Imunidades tributárias: análise crítica da imunidade tributária conferida as entidades educacionais - Silva, Filipe Piazzi Mariano (2017)
The following research is centered around a careful critical analysis pertaining to the tributary immunity established in the national judicial legislation, notably among those destined towards the philantropic, non-for-profit educational establishments, acting with the purpose of observing its development and constitution whilst aiming to identify if its development remains aligned with the social and judicial purposes which motivated them to begin with. Hence, we begin with a taxation historical outline, including the first manifestations of tributary immunity, thus allowing us to identify the reasons and adaptations to the current line of thought, where its acceptance must, compulsorily, relate to the access of its rights and warranties, thus acting in favor of the ensued absence of taxation capabilities related to its social relevance. Therefore we conclude with the analysis of the pertaining constitutional benefit within the tributary constitutional plan, ranging from, observations drawn from its judicial nature to the contemplation of the scope of its attributes, yet without doing away, albeit covering, in smaller scale, its modalities within the current Brazilian Constitution. In its latter sections, this study covers specific aspects of the logic between benefits accreted by the main entities of law, and what the benefited institutions give in return in favor of society at large, as it is irrefutable that, the tax exemption attributed to these institutions carries within it an increase in taxation to others many times doing so excessively, which should only be accepted within the limits measured by the benefits that such organization would bring to society and or due to the inability to carry regular taxation. This research conludes drawing upon simulations and research, that there is clear discrepancy in the relationship afore mentioned whereas the need for taxation regulation reform and reorganization becomes evident so that the system can continue to honor the taxation benefit to the organizations referred to, while the opposite seems inadmissible viewing from the current judicial and social standpoint.